Implementation of the MBKM Grant Program as an Effort to Empower the Community of Gentungan Village, Mojogedang, Karanganyar - Widarizki, Restik Bunga; Utami, Novi Tri; Zahroh, Nabila Shofiatuz; Asih, Nuri Luthfi; Pramesti, Mardiani Rahayu; Purwaningsih, Purwaningsih; Rosyida, Rohima Tazkiyah; Fathurrahmah, Nuzul Isnaini (Abdi Masyarakat, 2024)
This study aims to determine the implementation of the MBKM project grant program in the village as an effort to empower the community of Gentungan Village, Mojogedang District, Karanganyar Regency. The great potential of Gentungan Village is in terms of tourism, culture, and also a strategic location that makes this village have its own opportunities and attractions. Cultural insight by the community is also important to preserve the cultural heritage of the archipelago. This research was conducted with descriptive qualitative research methods and used data collection techniques in the form of observation. The MBKM Grant Program produces several work programs such as, internship programs at the village office, getting to know the variety of archipelago heritage through teaching activities, utilizing Rumah Eduwisata tours through outbound activities, kokedama skills training, and greening programs. The implementation of the MBKM Grant work program is able to encourage motivation, active participation, and optimize the local potential of the Gentungan Village community in a sustainable manner.